"Our Lady of Congo": The Creation and Reception of an Early Missionary Propaganda Devotion. (14th March 2020) - Petit, Pierre
Abstract: In 1891, the founder of the Matadi mission commissioned a master sculptor in Ghent to create a neo-gothic Madonna and child with a kneeling, imploring African released from the shackles of slavery at the Virgin's feet. "Our Lady of Congo" was expected by its creators to become the tutelary figure of the new colony. In Belgium, it was successfully used as missionary propaganda, notably by the Society for Congolese Children, a pious association settled in Ghent to ransom young slaves in the Congo Free State. Yet the sculpture only had mixed success in the Leopoldian colony. It took part in the creation of a nostalgic space for the missionaries of Matadi, but failed to elicit the devotedness of the local population, despite over three centuries of Kongo Christianity elaborated by the local elites and the Catholic missionaries. These divergent receptions are analyzed based on historical and visual sources, using comparative data to shed light on the representations of slavery, race, and redemption as appraised in Belgium and in Congo.